2020
DOI: 10.1007/s00415-020-09861-w
|View full text |Cite
|
Sign up to set email alerts
|

SPG7 mutations in amyotrophic lateral sclerosis: a genetic link to hereditary spastic paraplegia

Abstract: Amyotrophic lateral sclerosis (ALS) and hereditary spastic paraplegia (HSP) are motor neuron diseases sharing clinical, pathological, and genetic similarities. While biallelic SPG7 mutations are known to cause recessively inherited HSP, heterozygous SPG7 mutations have repeatedly been identified in HSP and recently also in ALS cases. However, the frequency and clinical impact of rare SPG7 variants have not been studied in a larger ALS cohort. Here, whole-exome (WES) or targeted SPG7 sequencing was done in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Familial ALS accounts for only 5%-10% of ALS cases, while sporadic ALS accounts for 90%-95% of cases [ 11 ]. Regardless of whether there is a family history, the disease pathogenesis is related to mutations in genes including SOD1 [ 7 , 12 ], OPTN [ 6 , 13 ], UBQLN2 [ 11 ], C9orf72 [ 8 ], SQSTM1 [ 2 ], SETX [ 2 ], GARP [ 9 ], PFN1 [ 14 ], and SPG7 [ 15 ] and genes that encode RNA-binding proteins [ 16 ], such as TARDBP , hnRNPA2B1 , hnRNPA1 , and FUS .…”
Section: Introductionmentioning
confidence: 99%
“…Familial ALS accounts for only 5%-10% of ALS cases, while sporadic ALS accounts for 90%-95% of cases [ 11 ]. Regardless of whether there is a family history, the disease pathogenesis is related to mutations in genes including SOD1 [ 7 , 12 ], OPTN [ 6 , 13 ], UBQLN2 [ 11 ], C9orf72 [ 8 ], SQSTM1 [ 2 ], SETX [ 2 ], GARP [ 9 ], PFN1 [ 14 ], and SPG7 [ 15 ] and genes that encode RNA-binding proteins [ 16 ], such as TARDBP , hnRNPA2B1 , hnRNPA1 , and FUS .…”
Section: Introductionmentioning
confidence: 99%
“…Spastic paraplegia 7 (SPG7) is the first‐identified autosomal recessive (AR) type of HSP, accounting for 5%–12% of AR‐HSP 4 . Pathogenic variants in SPG7 may also lead to spastic and/or cerebellar ataxia, peripheral neuropathy with no other neurological symptoms, primary progressive multiple sclerosis, amyotrophic lateral sclerosis, primary lateral sclerosis, parkinsonism, limb dystonia, and isolated dominant optic atrophy 5‐13 . Although the inheritance of SPG7 is considered to be AR, several reports suggested that SPG7 variants may also cause autosomal dominant (AD) HSP 5,14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Pathogenic variants in SPG7 may also lead to spastic and/or cerebellar ataxia, peripheral neuropathy with no other neurological symptoms, primary progressive multiple sclerosis, amyotrophic lateral sclerosis, primary lateral sclerosis, parkinsonism, limb dystonia, and isolated dominant optic atrophy. [5][6][7][8][9][10][11][12][13] Although the inheritance of SPG7 is considered to be AR, several reports suggested that SPG7 variants may also cause autosomal dominant (AD) HSP. 5,[14][15][16] None of these studies examined the possibility of digenic inheritance (carrying two mutations in different HSP genes), therefore the role of SPG7 in AD-HSP remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, certain genetic aberrations have been reported to modify the ALS phenotype, suggesting that genetic factors also shape the clinical presentation of ALS [ 4 ]. Moreover, some of the genes identified in ALS patients are also causative for other neurodegenerative disorders, such as C9orf72 and TARDBP for frontotemporal dementia (FTD) and Parkinson’s disease, and SPG7 and SPG11 for hereditary spastic paraplegia, indicating shared pathomechanisms [ 4 , 5 , 6 , 7 ]. In fact, it appears as though most, if not all ALS genes may be pleiotropic [ 8 ].…”
Section: Introductionmentioning
confidence: 99%